Works analysis in training design - Vincent Boccara; Catherine Delgoulet (Activités)
The aim of this article is to present and discuss a works analysis approach. This approach was developed within the context of a design project aiming to build a virtual environment for training (VET) workers involved in the assembly of aircraft parts. The frameworks of ergonomics and professional didactics served as a background for this study which took place in three stages: 1) an analysis of both demand and project, 2) work analysis (trainers, trainees and production unit workers, and 3) a co-analysis device to co-analyse work knowledge and its transmission by trainers. During the study, the focal point of work analysis, the people concerned and the results produced by ergonomists all evolved and became more complex. Using reflection on our own ergonomic practice, we discuss the benefits of works analysis as a means of identifying the wide range of training situations and of taking part in design projects.